Pemanfaatan Citra Satelit Landsat untuk Analisis Kerapatan Vegetasi Menggunakan Metode NDVI di Kota Serang Tahun 2014 dan 2024 - Ruuhulhaq, Muhammad Saiful; Setianingrum, Sarah (Universitas Pendidikan Ganesha, 2024)
Analyzes vegetation density changes in Serang City (2014-2024) using Landsat satellite imagery and the Normalized Difference Vegetation Index (NDVI). The research aims to assess urban vegetation degradation patterns and compliance with Indonesia's 30% green space regulation (UU No. 26/2007). Results show significant vegetation loss, with high-density vegetation (NDVI ≥0.45) decreasing from 7,481 ha (2014) to 4,814 ha (2024), while non-vegetated areas increased from 1,331 ha to 3,642 ha. The NDVI analysis reveals a 35.6% reduction in high-density green areas, primarily due to urban expansion. Methodologically, the study employs radiometrically-corrected Landsat-8 OLI data (bands 4-Red and 5-NIR) processed in a GIS environment, validated through Google Earth. The findings highlight urgent needs for urban green space rehabilitation and stricter land-use policies. This research contributes to sustainable city planning by providing a decade-long vegetation change baseline using remote sensing technology. Future studies should incorporate ground-truth verification and climate variables for comprehensive analysis.